2009
DOI: 10.1051/0004-6361/200911994
|View full text |Cite
|
Sign up to set email alerts
|

Integral field spectroscopy with SINFONI of VVDS galaxies

Abstract: Aims. This work aims to provide a first insight into the mass-metallicity (MZ) relation of star-forming galaxies at redshift z ∼ 1.4. To reach this goal, we present a first set of nine VVDS (VIMOS VLT Deep Survey) galaxies observed with the NIR integral-field spectrograph SINFONI on the VLT. Results. We find a typical shift of 0.2−0.4 dex towards lower metallicities for the z ∼ 1.4 galaxies, compared to the MZ-relation in the local universe as derived from SDSS data. However, this small sample does not show an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
46
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 53 publications
3
46
1
Order By: Relevance
“…In order to estimate gas phase metallicities of distant galaxies, they must have high surface brightnesses in their emission line gas (see Lehnert et al 2009, and references therein ). It is now reasonably well established that the mass-metallicity relation appears to have evolved over the last 10 Gyr (Savaglio et al 2005;Erb et al 2006;Mannucci et al 2009;Rodrigues et al 2008;Halliday et al 2008;Queyrel et al 2009). However, combining the possible limitations in the observations due to surface brightness dimming and the importance of mergers in initiating intense (high surface brightness) starbursts, it may be the determinations of the evolution in metallicity may be strongly influenced by dilution.…”
Section: Discussionmentioning
confidence: 95%
“…In order to estimate gas phase metallicities of distant galaxies, they must have high surface brightnesses in their emission line gas (see Lehnert et al 2009, and references therein ). It is now reasonably well established that the mass-metallicity relation appears to have evolved over the last 10 Gyr (Savaglio et al 2005;Erb et al 2006;Mannucci et al 2009;Rodrigues et al 2008;Halliday et al 2008;Queyrel et al 2009). However, combining the possible limitations in the observations due to surface brightness dimming and the importance of mergers in initiating intense (high surface brightness) starbursts, it may be the determinations of the evolution in metallicity may be strongly influenced by dilution.…”
Section: Discussionmentioning
confidence: 95%
“…The relation between galaxy mass and metallicity, which was first discovered by Lequeux et al (1979) in irregular galaxies, exists for star-forming galaxies both in the nearby universe (Tremonti et al 2004;Lamareille et al 2004) and at high redshifts z ∼ 0.7−3 (Lamareille et al 2006Queyrel et al 2009;Erb et al 2006;Maiolino et al 2008;Mannucci et al 2009). This trend by more massive galaxies toward higher gas-phase metallicity can be explained by This work is based on observations collected at the European Southern Observatory (ESO) Very Large Telescope, Paranal, Chile, as part of the Programs 179.A-0823, 78.A-0177, and 75.A-0318.…”
Section: Introductionmentioning
confidence: 90%
“…Recent observations have suggested that A&A 539, A93 (2012) galaxies involved in merging events show lower nuclear metallicities that are caused by the infall of pristine gas into the nucleus. Merging events could also account for outliers to the mass-metallicity relation (Kewley et al 2006;Michel-Dansac et al 2008;Peeples et al 2009;Queyrel et al 2009;Alonso et al 2010;Montuori et al 2010;Kewley et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For the explanation of the N/O redshift evolution, Queyrel et al (2009), Masters et al (2014), and Yabe et al (2015) have estimated N/O ratios at z ∼ 2, and have claimed the increase of N/O at fixed O/H. The excessive N/O ratios at fixed O/H may be caused by the decrease of O/H due to the pristine gas inflow into galaxies with rich nitrogen gas produced by the secondary nucleosynthesis, while Wolf-Rayet (WR) stars can produce the nitrogen in a time scale shorter than the oxygen production time scale in supernovae (Andrews & Martini 2013).…”
Section: Introductionmentioning
confidence: 99%